Role of obinutuzumab exposure on clinical outcome of follicular lymphoma treated with first‐line immunochemotherapy - Jamois, Candice (Br J Clin Pharmacol, 2019)
AIMS: Obinutuzumab (G) is a humanized type II, Fc‐glycoengineered anti‐CD20 monoclonal antibody used in various indications, including patients with previously untreated front‐line follicular lymphoma. We investigated sources of variability in G exposure and association of progression‐free survival (PFS) with average concentration over induction (C(meanIND)) in front‐line follicular lymphoma patients treated with G plus chemotherapy (bendamustine, CHOP, or CVP) in the GALLIUM trial. METHODS: Individual exposures (C(meanIND)) were obtained from a previously established population pharmacokinetic model updated with GALLIUM data. Multivariate Cox proportional hazard models and univariate Kaplan–Meier plots investigated relationships of PFS with exposure and other potential prognostic factors. RESULTS: Overall, G exposure was lower in high body‐weight patients and in males, and slightly lower in patients with high baseline tumour burden. Analysis of clinical outcomes showed that variability in G exposure did not impact PFS in G‐bendamustine‐treated patients; PFS was inferior in males and patients with FCGR2a/2b T232 T low‐affinity receptor variant, and superior in patients with FCGR2a/2b I232T variant. In G‐CHOP/CVP arms, PFS improved with increasing C(meanIND) (hazard ratio = 1.74 and 0.394 at 5(th) and 95(th) percentile compared to median C(meanIND)) and was inferior in patients with high baseline tumour size and B symptoms. CONCLUSIONS: It remains unclear whether for G‐CHOP/CVP patients lower G exposure is a consequence of adverse disease biology and/or resistance to chemotherapy backbone (higher clearance in nonresponder patients, as demonstrated for rituximab) rather than being the cause of poorer clinical outcome. A study with >1 dose level of G could help resolve this uncertainty.